The Effectiveness of using PAUT for Student Recruitment Management at Kolej Komuniti Selayang - Hanapiah, M. N.; Hashim, A.; Wahab, D. (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2024)
Nowadays technology its importance all service in many sectors. This study focuses on the application management and recruitment of new students. This study aims to evaluate the effectiveness of the "Your Application First" PAUT mobile application in process for new student registration session 2 2023/2024 at Kolej Komuniti Selayang (KKSY). This study was made based on the situation that occurred during the COVID-19 pandemic era where it was difficult for students to get relevant information and also from the aspect of application. Thus, this system can help the new student’s admissions committee and the who will register from anywhere and at any time. The data of this study were obtained quantitatively through the questionnaire method. The questionnaire was randomly distributed to 86 respondents consisting of new students who had registered. This study uses a descriptive method to assess users' perception of the effectiveness of the PAUT application. Data for this study were analyzed using percentage scores. The findings of the study showed that the average percentage of scores for all items of satisfaction with the use of PAUT was at a high level of 86.82%. The results of the study found that the effectiveness of this application in recruitment management showed that respondents agreed with the use of this application. The study also found that the use of this application for recruitment management is very good and satisfying. Overall, it was found that this application is an alternative platform that can help channel simple and easy-to-use information application process for new students at KKSY. It is proposed that in the future, a study can be conducted on the effectiveness of the use of the application in other community colleges to see what other factors can contribute to the improvement of the existing management system.